Knockout of mouse receptor accessory protein 6 leads to sperm function and morphology defects. Issue 6 (26th February 2020) - Devlin, Darius J; Agrawal Zaneveld, Smriti; Nozawa, Kaori; Han, Xiao; Moye, Abigail R; Liang, Qingnan; Harnish, Jacob Michael; Matzuk, Martin M; Chen, Rui
Abstract: Receptor accessory protein 6 (REEP6) is a member of the REEP/Ypt-interacting protein family that we recently identified as essential for normal endoplasmic reticulum homeostasis and protein trafficking in the retina of mice and humans. Interestingly, in addition to the loss of REEP6 in our knockout (KO) mouse model recapitulating the retinal degeneration of humans with REEP6 mutations causing retinitis pigmentosa (RP), we also found that male mice are sterile. Herein, we characterize the infertility caused by loss of Reep6 . Expression of both Reep6 mRNA transcripts is present in the testis; however, isoform 1 becomes overexpressed during spermiogenesis. In vitro fertilization assays reveal that Reep6 KO spermatozoa are able to bind the zona pellucida but are only able to fertilize oocytes lacking the zona pellucida. Although spermatogenesis appears normal in KO mice, cauda epididymal spermatozoa have severe motility defects and variable morphological abnormalities, including bent or absent tails. Immunofluorescent staining reveals that REEP6 expression first appears in stage IV tubules within step 15 spermatids, and REEP6 localizes to the connecting piece, midpiece, and annulus of mature spermatozoa. These data reveal an important role for REEP6 in sperm motility and morphology and is the first reported function for a REEP protein in reproductive processes. Additionally, this work identifies a new gene potentially responsible for human infertility and has implications for patients with RP harboring mutations in REEP6 . Abstract : Receptor accessory protein 6 is essential for sperm motility, morphology, and penetration of the zona pellucida in mice.